HUWE1 E3 ligase promotes PINK1/PARKIN-independent mitophagy by regulating AMBRA1 activation via IKKα - Di Rita, Anthea; Peschiaroli, Angelo; D′Acunzo, Pasquale; Strobbe, Daniela; Hu, Zehan; Gruber, Jens; Nygaard, Mads; Lambrughi, Matteo; Melino, Gerry; Papaleo, Elena; Dengjel, Jörn; El Alaoui, Said; et al. (Nature communications, 2018)
The selective removal of undesired or damaged mitochondria by autophagy, known as mitophagy, is crucial for cellular homoeostasis, and prevents tumour diffusion, neurodegeneration and ageing. The pro-autophagic molecule AMBRA1 (autophagy/beclin-1 regulator-1) has been defined as a novel regulator of mitophagy in both PINK1/PARKIN-dependent and -independent systems. Here, we identified the E3 ubiquitin ligase HUWE1 as a key inducing factor in AMBRA1-mediated mitophagy, a process that takes place independently of the main mitophagy receptors. Furthermore, we show that mitophagy function of AMBRA1 is post-translationally controlled, upon HUWE1 activity, by a positive phosphorylation on its serine 1014. This modification is mediated by the IKKα kinase and induces structural changes in AMBRA1, thus promoting its interaction with LC3/GABARAP (mATG8) proteins and its mitophagic activity. Altogether, these results demonstrate that AMBRA1 regulates mitophagy through a novel pathway, in which HUWE1 and IKKα are key factors, shedding new lights on the regulation of mitochondrial quality control and homoeostasis in mammalian cells. Mitophagy is crucial for mitochondrial quality control and maintenance of cellular homeostasis. Here the authors identify an E3 ubiquitin ligase, HUWE1, that collaborates with LC3-interacting protein AMBRA1 to induce mitochondrial clearance.